Produk Penggilingan Biji-Bijian untuk Meminimalkan Biaya Produksi dalam Bisnis Peternakan - Rahmi Meilina Sari; Khalida Syahputri; Indah Rizkya Tarigan; Inggrita Gusti Sari Nasution (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
The main supply of indonesian food comes from agricultural and livestock products. One of the sources of body protein that is favored by the public from the livestock sector, one of which is poultry farming. Egg and meat commodities from poultry have excellent market prospects because prices are relatively cheap and easy toobtain. One of the keys to the success of poultry is the timely and high-nutrient feeding that contains high levels of protein. IKA Livestock Business spends Rp5.400.000 for animal feed costs every month. The high cost makes partners mix feed with corn. But large corn grains are difficult to digest so it requires simple technology that is able to break down corn. To encourage the improvement of efficiency through modification of animal feed so that the implementation of science and technology that is able to provide results in the form of grain grinder machine to overcome the problem of animal feed. In addition to creating this devotional tool also provides training on financial management by bookkeeping and the creation of machine usage and maintenance procedures so that performance is maintained and has a long service life.